ANALYSIS OF NON-CONFORMITIES IN THE PROCESSING OF INDUSTRIALIZED FIGS (FICUS CARICA) (REMUNOM, 2024)
This work originated due to the large occurrence of failures in the industrial process, which was stipulated as non-conformity, this fact when occurred, in addition to causing inconvenience in the production of the product, would still undermine the reliability of consumers and customers, denigrating the reputation and image of the company. All the negative actions generated by a non-conformity would lead to the loss of customers and business opportunities. What's more, a lack of commitment in the industrialization process can damage the company's credibility and reduce its competitive position. In order to achieve a safe process, so that the product reaches the consumer's table with quality, we must design the execution of the process with the utmost attention, avoiding and/or minimizing non-conformities. By accessing that during the process undue changes may occur, known in the industrial environment as: non-conformity (NC), action plans are adopted after careful analysis of the degree of risk of each stage, they must be designed with clarity of idea, avoiding doubts when being executed, In this study we sought to identify the most critical points of an industrial process that generates conflicts if not well directed by the leadership, it also shows us the importance of the manager having knowledge of the entire flow of each product.